The effect of Lycium barbarum polysaccharides (LBP) on the vitrification cryopreservation efficiency of bovine oocytes - Zhihong Cao; Linli Xiao; Jiahua Bai; Yusheng Qin; Kexiong Liu; Yan Liu; Xiaoling Xu (Theriogenology, 2026)

Association of 17β-HSD3 with steroidogenesis-related gene expression and primordial germ cell development in ducks - Li Li; Xiaopan Liu; Linli Zhang; Liang Huang; Zhongwei Miao; Zhiming Zhu; Qinlou Huang; Qingwu Xin; Nenzhu Zheng (Theriogenology, 2026)

Solidification of Heavy Metals During the Calcination of Washed Municipal Solid Waste Incineration Fly Ash with Montmorillonite Addition - Zehua Zhao; Yi Wang; Dapeng Zhang; Linli Liu; Yifan Xu; Houhu Zhang; Ganghua Pan; Zhicheng Zhu (Water, Air, & Soil Pollution, 2026)

Enhanced piezocatalytic hydrogen production of molybdenum disulfide by metal organic framework-derived magnetic NiFe2O4@carbon nanohybrids - Linli Hou; Wenting Zhang; Mang Lu; Huanggen Yang; Limin Liu (Journal of Environmental Chemical Engineering, 2026)

Genomic and phenotypic analysis of stress-tolerant, aroma-producing yeast screened under low-aw, low-moisture content for low-salt chili fermentation - Xin Wang; Linli Dai; Jae-Hyung Mah; Wen Qin; Shuxiang Liu (Food Research International, 2026)

Sex-specific differences in cadmium accumulation and responses in the freshwater snail Cipangopaludina cathayensis - Wei Jinyou; Xiang Shanshan; Yu Jing; Li Linli; Tan Haizhen; Ye Quanqing; Yang Liu; Deng Yufan; Cui Jiaming; Wu Zhengjun; Jiang Jiaoyun (Chemico-Biological Interactions, 2026)

Meta-analysis of Probiotic Interventions in Roux-en-Y Gastric Bypass and Sleeve Gastrectomy: Effect on Cardiovascular Risk Factors - Banghao Xie; Hong Yong; Qi Liu; Linli Hu; Meixue Yang (Probiotics and Antimicrobial Proteins, 2026)

Overcoming mechanical and moisture barriers: A novel rice protein/sodium alginate packaging film based on gelatin and PDMS - Linli Wei; Xiaoli Qin; Jingwen Li; Xinjia Zhou; Xiong Liu; Jinfeng Zhong (Food Chemistry, 2026)

Effects of chrononutrition on aging and lifespan - Yiming Wang; Siyu Zhang; Ping Xiang; Gaoyu Liu; Aiman Yu; Hanxi Yuan; Linli Jiang; Dan Shi (Food Research International, 2026)

BAMBI modulates proliferation, apoptosis, and hormone secretion in Jinding duck granulosa cells - Li Li; Xiaopan Liu; Changtao Liu; Chengfu Pan; Linli Zhang; Qingwu Xin; Zhongwei Miao; Liang Huang; Yuwei Li; Yaping Zhang; Qinlou Huang; Nenzhu Zheng; et al. (Animal Reproduction Science, 2026)

Relationship between DNA methylation and ethylene in plants: A review - Xinmeng Geng; Zesheng Liu; Caiting An; Min Cao; Qi Wang; Mengkun Liu; Qianbing Li; Chunlei Wang; Linli Hu (Plant Science, 2026)

Multi-omics characterization of benzo[a]pyrene toxicity networks identifies SERPINE1 and STK3 as prognostic biomarkers and therapeutic targets in head and neck squamous cell carcinoma - Yan Guo; Jiarui Zhang; Jingchun Ge; Liang Li; Ming Liu; Linli Tian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Acid-induced structural reorganization of fish myofibrillar protein gels: trade-off between elasticity and stability - Linli Fang; Ruoyi Hao; Xinlin Liu; Xianbing Xu; Shengjie Li; Xuanpeng Wang; Dan Wang; Yugang Wang; Hairong Sun; Xiuping Dong; Jinfeng Pan (Food Research International, 2026)

De novo synthesis of tryptanthrin and its derivatives from indole: engineering a sustainable photocatalytic strategy - Ya Zhou; Junrong Zhang; Ya Xiao; Hongwu Liu; Guoqing Wang; Linli Yang; Wujun Jian; Dan Zeng; Xiang Zhou; Song Yang (Molecular Diversity, 2026)

OsTIP1;2 is a key regulator of rice seed germination and stress resilience - Xin Liu; Linli Ben; Siyuan Tang; Yingbo Gao; Xiaoxiang Zhang; Guichun Dong; Juan Zhou; Zefeng Yang; Yong Zhou; R. Glen Uhrig; Jianye Huang; Youli Yao (Plant Science, 2026)

Temperature as a determinant of symbiodiniaceae health: physiological, antioxidant, and metabolic responses under co-exposure to microplastics - Tan Haizhen; Tian Wenfei; Liu Tingting; Li Lixiang; Ye Quanqing; Wei Jinyou; Li Linli; Wei Fen; Jiang Jiaoyun (Marine Environmental Research, 2026)

Mining of trace natural products from Pyrrosia calvata with feature-based molecular network strategy - Yan Li; Boquan Qu; Dian Liu; Feifei Huang; Linli Xu; Yanfang Liu (Biochemical Systematics and Ecology, 2025)

The importance of soil depth in determining the impacts of mixed plantations with thinning on soil multifunctionality - Guangqiu Cao; Linli Dai; Jingwen Qiu; Tingting Peng; Yongkang Wang; Jiangchun Liu; Carolina Urbina Malo; Yiquan Ye; Qing-Fang Bi (Plant and Soil, 2025)
Background and aims Mixed plantations are known to enhance ecosystem functions compared to monocultures, yet their effects on microbial community, soil organic carbon (SOC) quality, and soil multifunctionality across soil profiles remain unclear. This study explores how mixed plantation combined with thinning influence both above- and belowground litter inputs, and how these affect the dynamics of SOC, microbial activities, and ultimately, soil multifunctionality in subtropical Chinese fir plantations. Methods We analyzed tree growth and litter inputs, active SOC pools, nutrient dynamics, enzyme activities, microbial communities, and soil properties across soil profiles under three management practices: monoculture, thinning, and mixed plantation combined with thinning. Key drivers of active SOC and soil multifunctionality were identified using random forest and structural equation modeling. Results Mixed plantations with thinning enhanced tree productivity and root biomass, reduced litterfall, and promoted active SOC and soil multifunctionality, especially at intermediate soil depths (20–40 cm). These effects were linked to a lower ratio of oxidoreductase to carbohydrase activities and higher microbial diversity. Soil depth emerged as a dominant factor shaping microbial activity and community composition, with its interaction with soil properties significantly influencing active SOC and soil multifunctionality. Structural equation modeling further revealed that active SOC dynamics were strongly correlated with soil multifunctionality across the soil profile. Conclusions Mixed plantations alleviate depth-related constraints on soil processes, improving the microbial roles in promoting active SOC and soil multifunctionality. These findings highlight the potential of mixed plantations to enhance soil health and ecosystem services, particularly in monoculture-dominated systems.

CRP and HNF1A collaborate to regulate the progression of laryngeal cancer through the Wnt signaling pathway - Zhigang Zhao; Xiaojing Zhu; Jinyuan Xu; Penglong Song; Yanan Sun; Zhenming Yang; Li Wang; Jiarui Zhang; Rui Zhao; Xiaoxue Chen; Wenjing Li; Linli Tian; et al. (Functional & Integrative Genomics, 2025)

Natural-product repurposing for novel reactive oxygen species inducer discovery: bactericidal profiling and structure-activity relationship of ellipticine and its analogs - Jingsha Yang; Guoqing Wang; Yi He; Wan Chen; Hongwu Liu; Linli Yang; Dan Zeng; Zhibing Wu; Liwei Liu; W.M.W.W. Kandegama; Zhenbao Luo; Xiang Zhou; et al. (Physiological and Molecular Plant Pathology, 2025)

Ceritinib (LDK378) inhibits laryngeal squamous cell carcinoma progression via regulating ROS-induced mitochondrial apoptosis and inducing oxidative stress - Yue Wang; Xiaoli Ren; Pengyan Liu; Ran An; Wenjing Li; Licheng Xu; Yaoyao Dong; Xiaolin Xu; Yi wang; Lei Zhang; Linli Tian (Toxicology and Applied Pharmacology, 2025)

Efficient activating peracetic acid by copper-aluminum composites to degrade sulfathiazole: The critical role of Cu(III) species - Yuxiao Mu; Yanping Ding; Linli Tan; Qiulin Shi; Lei Chen; Jiaqi Ding; Jingwen Wang; Yong Liu; Pengchao Xie (Journal of Environmental Chemical Engineering, 2025)

Effect of the new fixed-time artificial insemination technology based on novel hormone preparations in gilts - Kexiong Liu; Hanbing Zhang; Xiaoling Xu; Zheng Huang; Feng Ji; Yusheng Qin; Linli Xiao; Shiwen Chen; Miaomiao Yan; Peng Zhao; Suozi Ge; Jiani Shu; et al. (Animal Reproduction Science, 2025)

Flexural behavior of steel plate-UHPC composite wet joints for precast UHPC deck slabs - Minghong Qiu; Zongxuan Shao; Banfu Yan; Youshan Liu; Linli Duan; Zhao Li (Engineering Structures, 2025)

Carbon dots modified metallated graphdiyne with enhanced electron transfer and O2 adsorption capacity for efficient H2O2 photoproduction - Honglin Si; Mude Zhu; Zenan Li; Jiaxuan Wang; Jiacheng Li; Linli Xu; Hui Huang; Yang Liu; Wai-Yeung Wong; Zhenhui Kang (Chemical Engineering Journal, 2025)

Impact of pivot selection and lexicon utilization on pivot profile analysis of food off-odor reduction: The case of soymilk - Chang Liu; Linli Bu; Chen Wang; Hongwei Wang; Huayi Suo (Food Quality and Preference, 2025)

OsBSK3 and OsBSK2 regulate grain size and leaf angle via MAPK signaling pathway in rice - Xin Jin; Linli Fu; Chunxiao Chen; Jiali Liu; Yingxiang Liu; Wei Zhang; Xiufeng Li; Changhua Liu; Qingyun Bu; Xiaojie Tian (Theoretical and Applied Genetics, 2025)

Based on the resting-state functional magnetic resonance imaging reveals the causal relationship between the brain function network and the risk of tinnitus: a bidirectional Mendelian randomization analysis - Yuchao Liu; Chunli Li; Linli Yao; Yuan Tan; Lu Shi; Pei Chen (Brain Imaging and Behavior, 2025)

Ambient volatile organic compounds in a typical industrial city in southern China: Impacts of aromatic hydrocarbons from new industry - Jian Sun; Qin Peng; Zezhi Peng; Linli Qu; Zhou Zhang; Weiwei Liu; Steven Sai Hang Ho (Science of The Total Environment, 2024)

Improving the value of planting and breeding waste compost in agricultural applications: A zucchini cultivation case and circular agricultural models analysis - Jianzhong Tie; Xueqin Gao; Yayu Liu; Wenxu Chen; Linli Hu; Jihua Yu; Tianlai Li (Chemical Engineering Journal, 2024)

Ciprofloxacin Accelerates Angiotensin-II-Induced Vascular Smooth Muscle Cells Senescence Through Modulating AMPK/ROS pathway in Aortic Aneurysm and Dissection - Weiyue Zeng; Yaowen Liang; Shangjun Huang; Jiarui Zhang; Cong Mai; Binbin He; Linli Shi; Baojuan Liu; Weifeng Li; Xiaoran Huang; Xin Li (Cardiovascular Toxicology, 2024)

Determination and analysis of patulin in apples, hawthorns, and their products by high-performance liquid chromatography - Yanan Zhao; Wenjing Xu; Ruihua Liu; Linli Guo; Ping Liu (Mycotoxin Research, 2024)

Comprehensive evaluation on effect of planting and breeding waste composts on the yield, nutrient utilization, and soil environment of baby cabbage - Yali Qiao; Jianzhong Tie; Xuehua Wang; Baihong Wei; Wenbin Zhang; Zeci Liu; Guobin Zhang; Jian Lyu; Weibiao Liao; Linli Hu; Jihua Yu (Journal of Environmental Management, 2023)

Environmental and health impacts of household energy conversion on PAHs and their derivatives in PM2.5 in typical areas of northern China - Yunlong Bai; Hongmei Xu; Rong Feng; Yunxuan Gu; Meixuan Liu; Jian Sun; Linli Qu; Steven Sai Hang Ho; Zhenxing Shen; Junji Cao (Science of The Total Environment, 2023)

Chemical composition and potential health risks of tire and road wear microplastics from light-duty vehicles in an urban tunnel in China - Meixuan Liu; Hongmei Xu; Rong Feng; Yunxuan Gu; Yunlong Bai; Ningning Zhang; Qiyuan Wang; Steven Sai Hang Ho; Linli Qu; Zhenxing Shen; Junji Cao (Environmental Pollution, 2023)

Characteristics of PM2.5 and Its Reactive Oxygen Species in Heating Energy Transition and Estimation of Its Impact on the Environment and Health in China—A Case Study in the Fenwei Plain - Zexuan Wang; Hongmei Xu; Rong Feng; Yunxuan Gu; Jian Sun; Suixin Liu; Ningning Zhang; Dan Li; Tao Wang; Linli Qu; Steven Sai Hang Ho; Zhenxing Shen; et al. (Advances in Atmospheric Sciences, 2023)

OsUGE1 is directly targeted by OsGRF6 to regulate root hair length in rice - Shuaiqi Yang; Nuo Xu; Nana Chen; Jiaxuan Qi; Abdul Salam; Junyu Wu; Yihua Liu; Linli Huang; Bohan Liu; Yinbo Gan (Theoretical and Applied Genetics, 2023)

Deposition effect of inhaled particles in the human: Accurate health risks of personal exposure to PAHs and their derivatives from residential solid fuel combustion - Rong Feng; Hongmei Xu; Yunxuan Gu; Min Gao; Yunlong Bai; Meixuan Liu; Zhenxing Shen; Jian Sun; Linli Qu; Steven Sai Hang Ho; Junji Cao (Atmospheric Environment, 2023)

Research on the Evaluation of Logistics Efficiency in Chinese Coastal Ports Based on the Four-Stage DEA Model - Hui Li; Linli Jiang; Jianan Liu; Dandan Su (Journal of Marine Science and Engineering, 2022)
In the context of economic globalization, coastal port logistics has gradually become a focus of economic development, and the proper management of coastal port logistics performance is the main way to realize the high-efficiency operation of coastal ports, drives the direct economic development of the hinterland, and enhances import and export trade market competitiveness. Accordingly, this study was aimed to measure port logistics efficiency and explore its path of improvement for China’s coastal ports during the 2014–2018 period with a four-stage DEA model, including a Tobit model. The results of this study show that most of the coastal ports in China have emphasized their size more than their planning. During the study period, improving road network construction and the economic level in hinterland port cities was conducive to improving port logistics efficiency, but tertiary industry investment and foreign trade levels were negatively correlated with coastal port logistics efficiency.

Analysis of spatial and temporal changes of vegetation cover and its driving forces in the Huainan mining area - Xuyang Zhang; Ying Liu; Xiaoyang Chen; Linli Long; Yongdong Su; Xiaokun Yu; Hongmei Zhang; Yongchun Chen; Shikai An (Environmental Science and Pollution Research, 2022)

The Variability of Air-sea O2 Flux in CMIP6: Implications for Estimating Terrestrial and Oceanic Carbon Sinks - Changyu Li; Jianping Huang; Lei Ding; Yu Ren; Linli An; Xiaoyue Liu; Jiping Huang (Advances in Atmospheric Sciences, 2022)
The measurement of atmospheric O 2 concentrations and related oxygen budget have been used to estimate terrestrial and oceanic carbon uptake. However, a discrepancy remains in assessments of O 2 exchange between ocean and atmosphere (i.e. air-sea O 2 flux), which is one of the major contributors to uncertainties in the O 2 -based estimations of the carbon uptake. Here, we explore the variability of air-sea O 2 flux with the use of outputs from Coupled Model Intercomparison Project phase 6 (CMIP6). The simulated air-sea O 2 flux exhibits an obvious warming-induced upward trend (∼1.49 Tmol yr −2 ) since the mid-1980s, accompanied by a strong decadal variability dominated by oceanic climate modes. We subsequently revise the O 2 -based carbon uptakes in response to this changing air-sea O 2 flux. Our results show that, for the 1990–2000 period, the averaged net ocean and land sinks are 2.10±0.43 and 1.14±0.52 GtC yr −1 respectively, overall consistent with estimates derived by the Global Carbon Project (GCP). An enhanced carbon uptake is found in both land and ocean after year 2000, reflecting the modification of carbon cycle under human activities. Results derived from CMIP5 simulations also investigated in the study allow for comparisons from which we can see the vital importance of oxygen dataset on carbon uptake estimations.

Exosomal miR-486-5p derived from human placental microvascular endothelial cells regulates proliferation and invasion of trophoblasts via targeting IGF1 - Ruixia Ma; Zhijiang Liang; Xiaomei Shi; Linli Xu; Xiaowei Li; Jinhua Wu; Lina Zhao; Guocheng Liu (Human Cell, 2021)
Preeclampsia (PE) is a serious complication of pregnancy. Exosomes are known to be upregulated in PE. In this study, we sought to investigate the effect of miR-486-5p from human placental microvascular endothelial cells, on the function of trophoblast cells. To investigate the function of human placental microvascular endothelial cell (HPVEC)-derived exosomes on trophoblast cells, HPVECs were treated with hypoxia/reoxygenation (H/R). The separation efficiency of exosomes was determined by transmission electron microscopy, nanosight and Western blot. Cell Counting Kit-8, EdU staining, wound-healing, and transwell assay were performed to detect the effect of exosomally transferred miR-486-5p inhibitor on proliferation, migration and invasion of trophoblast cells. MiRDB and dual-luciferase report assay were used to find the target of miR-486-5p. Our data revealed that miR-486-5p was significantly upregulated in H/R-treated HPVEC-Exo, and miR-486-5p was enriched in HPVEC-Exo. miR-486-5p inhibitor carried by HPVEC-Exo significantly inhibited the proliferation, migration and invasion of trophoblast cells. Insulin-like growth factor 1 (IGF1) was found to be the target of miR-486-5p, and IGF1 overexpression notably reversed the effect of miR-486-5p inhibitor from HPVEC-Exo on trophoblast cell function. In summary, H/R-treated HPVEC-derived exosomally expressing miR-486-5p inhibitor significantly inhibited the proliferation, migration and invasion of trophoblast cells via downregulation of IGF1. The findings from the present study may be useful in the development of treatments for PE.

Connective profiles and antagonism between dynamic and static connectivity underlying generalized epilepsy - Sisi Jiang; Hechun Li; Haonan Pei; Linli Liu; Zhiliang Li; Yan Chen; Xiangkui Li; Qifu Li; Dezhong Yao; Cheng Luo (Brain Structure and Function, 2021)

A multivariate pattern analysis of resting-state functional MRI data in Naïve and chronic betel quid chewers - Zeqiang Linli; Xiaojun Huang; Zhening Liu; Shuixia Guo; Adellah Sariah (Brain Imaging and Behavior, 2021)

NbGIS regulates glandular trichome initiation through GA signaling in tobacco - Yihua Liu; Dongdong Liu; Ali Raza Khan; Bohan Liu; Minjie Wu; Linli Huang; Junyu Wu; Ge Song; Hongwei Ni; Haiming Ying; Hao Yu; Yinbo Gan (Plant Molecular Biology, 2018)

Detection of respiratory syncytial virus fusion protein variants between 2009 and 2012 in China - Qiuling Xia; Lili Zhou; Caijing Peng; Rui Hao; Ke Ni; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Linli He; Daiyin Tian; Lijia Wang; et al. (Archives of Virology, 2014)

Intra-annual variations in abundance and species composition of carabid beetles in a temperate forest in Northeast China - Xiaowei Wang; Jörg Müller; Linli An; Lanzhu Ji; Yan Liu; Xugao Wang; Zhanqing Hao (Journal of Insect Conservation, 2014)

Effects of breeds and dietary protein levels on the growth performance, energy expenditure and expression of avUCP mRNA in chickens - Qihua Li; Zhiqiang Xu; L. Liu; Hongxin Yu; Hua Rong; Linli Tao; Xi Zhang; Xiaobo Chen; Dahai Gu; Yueyuan Fan; Xiaoqin Li; Changrong Ge; et al. (Molecular Biology Reports, 2013)